2020
DOI: 10.3390/ijerph17238988
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Connection Type and Platform Diameter on Titanium Dental Implants Fatigue: Non-Axial Loading Cyclic Test Analysis

Abstract: Two-pieces dental implants must provide stability of the implant-abutment-interface. The connection type and platform diameter could influence the biomechanical resistance and stress distribution. This study aims to evaluate the fatigue for different types of connections, external and internal, and different platform diameters. Three implant designs with the same length were used: (a) external hexagon/narrow platform; (b) internal double hexagon/narrow platform; (c) internal octagon/regular platform. A fatigue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The number of cycles was increased by a factor of approximately 7 according to the linear models, accepting the research hypothesis concerning implant platform diameter. These results were consistent with those of Nicolas-Silvente et al, 49 who reported lower stresses on the prosthetic screw with larger platform diameters. Nevertheless, the platform switching effect on peri-implant bone should be taken into account to avoid periimplant bone loss.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The number of cycles was increased by a factor of approximately 7 according to the linear models, accepting the research hypothesis concerning implant platform diameter. These results were consistent with those of Nicolas-Silvente et al, 49 who reported lower stresses on the prosthetic screw with larger platform diameters. Nevertheless, the platform switching effect on peri-implant bone should be taken into account to avoid periimplant bone loss.…”
Section: Discussionsupporting
confidence: 93%
“…48 As reported by Minatel et al, 47 a reduction of the IAC diameter (by using the platform switching concept) can result in higher stresses in the retaining screw. In addition, Nicolas-Silvente et al 49 performed experimental fatigue tests where the retaining screws were the failing components and concluded that a higher fatigue limit was obtained with wider platforms, even though this conclusion might be limited by the fact that the specimens tested had different connection types.…”
mentioning
confidence: 99%
“…Because of variations in stress in the clinical environment, it is difficult to predict this using in vitro models. Nicolas‐Silvente suggested that 5 mm diameter implants should be considered in these circumstances 28 …”
Section: Discussionmentioning
confidence: 99%
“…Nicolas-Silvente suggested that 5 mm diameter implants should be considered in these circumstances. 28 Clinical retrospective studies have examined the relationship between bone loss and cantilever length. 29,30 In these studies, the cantilevers are of 1 to 2 tooth lengths within the clinical guidelines of 7.5-15 and are considered treatment options with minimal loss of crestal bone.…”
Section: Discussionmentioning
confidence: 99%
“…Macroscopic design, especially that of the implant–abutment connections, has been considered as important for the success of dental implant treatment. External joints are a common feature in implant–abutment connections [ 10 ]. During mastication, the dental implant interacts with compressive force, which is parallel to the implant’s long axis and shearing force, which is not perpendicular to the implant’s long axis.…”
Section: Introductionmentioning
confidence: 99%